Studi Kandungan Bahan Tambahan Makanan Pada Minuman Thai Tea Di Sekitar Kampus Politeknik Kesehatan Muhammadiyah Makassar - Hayat, A. M. Fadhil; Sunu, Baharuddin; Abbas, Muhammad Ikbal; Islamia, Indah (Lontara Journal of Health Science and Technology, 2020)
Colorants are food additives that can improve or give color to foods. Sweeteners are synthetically processed artificial food additives that do not contain calories and a number of other nutritional values. These dyes and sweeteners can cause allergies such as cough, sensitive throat, and the most severe is impaired blood circulation. The purpose of this study was to determine the use of artificial coloring agents and artificial sweeteners in beverages around the Muhammadiyah Health Polytechnic Makassar. The method used in this research is descriptive and laboratory examination including: qualitative artificial dyes and quantitative artificial sweeteners. The results showed that, from the examination of 3 samples of artificial dyes, the use of Sunset Yellow was found. Meanwhile, from the examination of 2 samples of artificial sweeteners, there was no use of artificial sweeteners. Based on the results of research on Thai Tea drinks, it can be concluded that all samples examined were found to contain dyes made by Sunset Yellow. Meanwhile, from the sample examination, no artificial sweetener was found.